Information Content of Bank Credit Rating Changes: Evidence from Europe - Inkinen, Lauri (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This thesis examines the short-term impact of credit rating announcements on daily stock returns of 41 European banks indexed in STOXX Europe 600 Banks. The time period of this study is 2002–2015 and the ratings represent long-term issuer ratings provided by S&P, Moody’s and Fitch. Bank ratings are significant for a bank’s operation costs so it is interesting to investigate how investors react to changes in creditworthiness. The study objective is achieved by conducting an event study. The event study is extended with a cross-sectional linear regression to investigate other potential determinants surrounding rating changes. The research hypotheses and the motivation for additional tests are derived from prior research. The main hypotheses are formed to explore whether rating changes have an effect on stock returns, when this possible reaction occurs and whether it is asymmetric between upgrades and downgrades. The findings provide evidence that rating announcements have an impact on stock returns in the context of European banks. The results also support the existence of an asymmetry in capital market reaction to rating upgrades and downgrades. The rating downgrades are associated with statistically significant negative abnormal returns on the event day although the reaction is rather modest. No statistically significant reaction is found associated with the rating upgrades on the event day. These results hold true with both rating changes and rating watches. No anticipation is observed in the case of rating changes but there is a statistically significant cumulative negative (positive) price reaction occurring before the event day for negative (positive) watch announcements. The regression provides evidence that the stock price reaction is stronger for rating downgrades occurring within below investment grade class compared with investment grade class. This is intuitive as investors are more concerned about their investments in lower-rated companies. Besides, the price reaction of larger banks is more mitigated compared with smaller banks in the case of rating downgrades. The reason for this may be that larger banks are usually more widely followed by the public. However, the study results may also provide evidence of the existence of the so-called “too big to fail” subsidy that dampens the negative returns of larger banks.